A High‐Performance Self‐Powered UV‐Visible‐Infrared Broadband Photodetector Based on a Solution‐Processed Bi2Se3/Se Nanorods Heterojunction. Issue 16 (25th April 2022) - Fu, Zichun; Gao, Shiyong; Yuan, Ye; Lu, Huiqing; Ling, Duoduo; Ren, Shuai; Rong, Ping; Jiao, Shujie; Wang, Jinzhong; Zhang, Yong
Abstract: Nanostructured semiconductor materials synthesized through solution processes have received a substantial body of attention owing to their cost‐effectiveness, manufacturing ease, and environmental friendliness. Here, a simple solution approach is used to synthesize Bi2 Se3 /Se nanorods (NRs) heterojunction by covering Se NRs with a uniform Bi2 Se3 shell. The morphology, composition, and structure of the samples are characterized and the growth mechanism is also analyzed. Furthermore, the photodetector based on the Bi2 Se3 /Se NRs is fabricated. The as‐prepared Bi2 Se3 /Se NRs photodetector exhibits an outstanding broadband photoresponse from UV (365 nm) to IR (850 nm) with good repeatability and self‐powered ability. Upon light illumination, Bi2 Se3 /Se NRs photodetector shows maximum photocurrent of 190 µA (UV light), 194 µA (blue light), 145 µA (green light), 38 µA (red light), 4 µA (IR light) as well as a rapid response time around 0.1 s approximately. Moreover, a possible detection mechanism of Bi2 Se3 /Se NRs photodetector is also discussed. Abstract : Bi2 Se3 /Se nanorods heterojunction is successfully synthesized through a green and facile solution route. Moreover, a high performance self‐powered photodetector is fabricated based on the as‐prepared Bi2 Se3 /Se nanorods heterojunction. It can be realized that Bi2 Se3 /Se nanorods photodetector features the fast response speed and broadband photoresponse from the ultraviolet to infrared range.